The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1113/jp281187
|View full text |Cite
|
Sign up to set email alerts
|

AXIN1 knockout does not alter AMPK/mTORC1 regulation and glucose metabolism in mouse skeletal muscle

Abstract: Key points Tamoxifen‐inducible skeletal muscle‐specific AXIN1 knockout (AXIN1 imKO) in mouse does not affect whole‐body energy substrate metabolism. AXIN1 imKO does not affect AICAR or insulin‐stimulated glucose uptake in adult skeletal muscle. AXIN1 imKO does not affect adult skeletal muscle AMPK or mTORC1 signalling during AICAR/insulin/amino acid incubation, contraction and exercise. During exercise, α2/β2/γ3AMPK and AMP/ATP ratio show greater increases in AXIN1 imKO than wild‐type in gastrocnemius muscle.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…However, we found similar γ‐actin expression in the wild‐type and −/− lysate (Figure 1a), likely due to γ‐actin from other cell types dominating γ‐actin pool in whole‐muscle lysate. Thus, we next verified the effective excision of the floxed γ‐actin gene in myofibers by PCR similar to our previous studies (Li et al, 2021; Madsen et al, 2018). This yielded a ~50% reduction in floxed gene content in quadriceps muscle and ~30% in soleus (Figure 1b).…”
Section: Resultssupporting
confidence: 82%
“…However, we found similar γ‐actin expression in the wild‐type and −/− lysate (Figure 1a), likely due to γ‐actin from other cell types dominating γ‐actin pool in whole‐muscle lysate. Thus, we next verified the effective excision of the floxed γ‐actin gene in myofibers by PCR similar to our previous studies (Li et al, 2021; Madsen et al, 2018). This yielded a ~50% reduction in floxed gene content in quadriceps muscle and ~30% in soleus (Figure 1b).…”
Section: Resultssupporting
confidence: 82%
“…The significant obstacles of cardiomyocyte proliferation include: (1) stalled cell cycle, (2) specialized cytoskeleton, and (3) switched metabolic pathway [ 5 , 31 , 32 ]. Interestingly, AMPK is involved in all these three processes: AMPK senses energy stress and enhances catabolic metabolism [ 33 ]; AMPK mediates re-organization of the cytoskeleton [ 34 ], and AMPK inhibits cell proliferation [ 35 ]. Therefore, AMPK is one of the most critical elements in cardiomyocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…While it remains to be seen whether AXIN2 plays a redundant role in this process and regulates AMPK, Li et al . 13 reported no change in AMPK activation following AXIN1 imKO in the skeletal muscle. Furthermore, Zong et al .…”
Section: Gaps In Our Knowledgementioning
confidence: 96%
“…Interestingly, exercise-induced glucose uptake requires AXIN1 in skeletal muscles. While it remains to be seen whether AXIN2 plays a redundant role in this process and regulates AMPK, Li et al 13 reported no change in AMPK activation following AXIN1 imKO in the skeletal muscle. Furthermore, Zong et al 12 showed that AXIN2 could substitute AXIN1 in forming a complex between LKB1 and AMPK.…”
Section: Is Axin Expression Beneficial For Muscle Health?mentioning
confidence: 99%
See 1 more Smart Citation